The influence of transformational leadership on employee engagement in the context of hybrid work - Feriandy Feriandy (Annals of Human Resource Management Research, 2025)
Purpose: This study investigates how transformational leadership influences employee engagement in hybrid work environments, addressing a research gap in understanding leadership mechanisms that operate across both remote and in-office contexts. Methodology/approach: A mixed-methods design was employed by surveying 94 employees reduced from an initial 150 responses following data cleaning and conducting semi-structured interviews with 15 managers. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis to deepen the interpretation of the survey findings. Results/findings: The results show that transformational leadership, particularly through idealized influence and inspirational motivation, is positively associated with employee engagement in hybrid settings. Communication quality and trust function as key mediating factors that strengthen this relationship. Conclusion: The study concludes that transformational leadership plays a critical role in sustaining employee engagement within hybrid work arrangements. Effective communication and trust-building emerge as essential leadership practices for maintaining employee commitment across flexible work modalities. Limitations: The generalizability of the findings is constrained by the reduced sample size after data cleaning and the cross-sectional nature of the study. Contribution: This research contributes to the growing literature on hybrid work by contextualizing transformational leadership within blended work environments and by offering practical guidance for leaders seeking to foster engagement through communication and trust-building strategies.